A new transient simulation method of natural gas-condensate two-phase flow in pipeline network. (21st September 2020) - Shi, Guoyun; Fan, Di; Gong, Jing
Highlights: A method is developed to simulate the gas-condensate pipeline network. The method no longer requires the node mass balance equation to connect each pipe at the junction. The method can calculate the node pressure directly rather than iterative solution. The method can simulate the two-phase splitting flow of the gas-condensate. Abstract: Two-phase flow in pipeline network plays a significant role in the gathering system of the offshore natural gas-condensate field. However, the study of the transient numerical simulation of pipeline network is insufficient for flow assurance. Therefore, a transient simulation method is developed. The transient two-fluid model including an energy equation for two-phase flow is established firstly. Moreover, unlike pipeline, the node is an extra structure in the network. A corresponding method of discretizing the node domain and governing equations is therefore developed. In this way, the node pressure can be calculated directly rather than iteratively solved through a mass balance equation. Finally, a predict-correct two-phase flow algorithm is proposed. Moreover, a natural gas-condensate field pipeline network is applied to validate and verify the proposed method. Furthermore, a more complex network is simulated. The proposed method provides a reasonable result while the commercial code OLGA gives a divergent result.